The feeling of Loneliness and its relationship to some variables among Yemeni Students in China - Al-Dbyani, Aamer Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed at investigating the level of psychological loneliness, anxiety, depression, brief cope and social support, and the relationship between them among a sample of Yemeni students at Chinese Universities. The study sample consisted of some available (509) male and female students who were enrolled in the second semester of 2019-2020. The results showed a high level of psychological loneliness, and a significant positive correlation between psychological loneliness and anxiety, depression, and brief cope, while negative correlated with the social support. The results also showed statistically significant differences in the level of psychological loneliness and anxiety to gender in favor of females. In addition, the study found as well, differences in the level of brief cope and social support in favor of males, while there are no significant differences in the level of depression. The study concluded with a number of recommendations, the most important of which are: Supporting the cultural, social and sports activities of the Yemeni Students' Union in China to breaking social isolation and reducing the feeling of psychological loneliness among students.
Keywords: Loneliness; Anxiety; Depression; Brief Cope; Social Support; Yemeni students in China